Elaeis Guineensis 2022
DOI: 10.5772/intechopen.97862
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of the Oil Palm Cultivation in Cameroon

Abstract: Since 1990, oil palm cultivation, because nibbling large zones in dense forest areas of Cameroon, becomes the main driver of deforestation. It leads to the loss of plant and animal biodiversity as well as engaging soils and water pollution, which raises questions about its sustainability. Nowadays, palm plantations occupy almost 400 000 ha shared between agro-industries, elites and small farmers while annual palm oil production increased from 150, 000 tons in 2000 to 413,000 tons in 2018 against a demand that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The soil surface is exposed for the first few years before OPs mature as a result of deforestation, accentuating erosion and leaching. Soil texture and its biological characteristics are also modified during oil palm cultivation, which is often partly responsible for the degradation of plant diversity in oil palm plantations (Mesmin et al, 2021). Negative cultural impacts were recorded on cultural heritage and spiritual and religious services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil surface is exposed for the first few years before OPs mature as a result of deforestation, accentuating erosion and leaching. Soil texture and its biological characteristics are also modified during oil palm cultivation, which is often partly responsible for the degradation of plant diversity in oil palm plantations (Mesmin et al, 2021). Negative cultural impacts were recorded on cultural heritage and spiritual and religious services.…”
Section: Discussionmentioning
confidence: 99%
“…The most positive impact was recorded on food provisioning, as the oil palm fruits are usually eaten as a snack, and PO is used as an ingredient in a wide variety of dishes locally. In addition, palm wine is extracted from old oil palm trees and consumed widely by local people while the palm fronds are used as local raw materials for roofing (Hollier, 1984;Cheyns and Rafflegeau, 2005;Mesmin et al, 2021). Takoumbe et al (2023) in their recent study found the pseudo trunk of the tenera variety with the potential to be used in the implementation of insulating materials, reinforcement of composite materials, and in furnishing as wood.…”
Section: Discussionmentioning
confidence: 99%
“…The palm tree grows primarily in the forest area of southern Cameroon and in the littoral region. Oil palm grows best in Cameroon's coastal zone (southern, coastal, and southwestern regions) (Figure 12) [54]. Oil palm cultivation requires: (i) high daily temperatures throughout the year, ranging from 25 to 28 °C, with minimums of 18 °C in the coldest months; (ii) at least 5 hours of sunlight per day; and (iii) rainfall ranging from 1,800 to 2,400 mm/yr [53].…”
Section: The Case Of Socapalm Safacam Spfs Cdc and Pamolmentioning
confidence: 99%
“…Figure 12.Location of the major oil palm production basins in Cameroon (agro-industrial plantations)[54] …”
mentioning
confidence: 99%
“…Apart from shaping environmental sustainability [1][2][3], palm oil companies also significantly contribute to people's welfare by increasing their income and offering job opportunities [4,5]. However, these companies negatively affect the environment [4,6], disrupt water use in communities (Silalertruksa et al, 2017), shape smallholders' perceptions of land restoration activities [7], trigger changes in land cover [8], generate CO2 emissions [9], threaten biodiversity [10] and negatively affect other ecosystem services [11,12].…”
Section: Introductionmentioning
confidence: 99%